Antimicrobial use for selected diseases in cats in Switzerland - K. Schmitt; C. Lehner; S. Schuller; G. Schüpbach-Regula; M. Mevissen; R. Peter; C. R. Müntener; H. Naegeli; B. Willi (BMC Veterinary Research, 2019)
Abstract Background Antibiotic use in human and veterinary medicine is considered a main driver of antimicrobial resistance. Although guidelines to promote appropriate use of antimicrobials in veterinary patients have been developed, antibiotic overprescription is assumed to be a common problem. The goal of this study was to investigate antimicrobial use in cats in Switzerland with acute upper respiratory tract disease (aURTD), feline lower urinary tract disease (FLUTD) and abscesses, and to assess compliance of prescription with consensus guidelines. A total of 776 cases (aURTD, n = 227; FLUTD, n = 333; abscesses, n = 216) presented to two university hospitals and 14 private veterinary practices in Switzerland during 2016 were retrospectively evaluated. Clinical history, diagnostic work-up and antimicrobial prescription (class, dosage, duration) were assessed. Results A total of 77% (aURTD), 60% (FLUTD) and 96% (abscesses) of the cases received antibiotic therapy; 13–24% received combination or serial therapy. The cats were treated for a median of 7 (abscesses) and 10 days (aURTD, FLUTD). Treatments with potentiated aminopenicillins (40–64%), third generation cephalosporins (25–28%), aminopenicillins (12–24%) and fluoroquinolones (3–13%) were most common. Prescriptions were judged in complete accordance with consensus guidelines in 22% (aURTD), 24% (FLUTD) and 17% (abscesses) of the cases. Antibiotics were prescribed although not indicated in 34% (aURTD), 14% (FLUTD) and 29% (abscesses) of the cases. The presence of lethargy, anorexia or fever in cats with aURTD, and the detection of bacteriuria in cats with FLUTD were significantly associated with antibiotic therapy. Although diagnostic work-up was significantly more common (aURTD: university hospitals, 58%; private practices, 1%; FLUTD: university hospitals, 92%; private practices, 27%) and the use of critically important antibiotics significantly less common at the university hospitals (aURTD, 10%; FLUTD, 14%) compared to private practices (aURTD, 38%; FLUTD, 54%), the frequency of antibiotic treatment was not different between the university hospitals and private practices. Conclusions Our results indicate that overprescription of antibiotics in cats in Switzerland is common and accordance with guidelines is poor. The study highlights the need to promote antimicrobial stewardship in small animal medicine.